Nicotiana benthamiana as a model plant host for Xylella fastidiosa: Control of infections by transient expression and endotherapy with a bifunctional peptide - Baró, Aina; Saldarelli, Pasquale; Saponari, Maria; Montesinos, Emilio; Montesinos, Laura (Frontiers in Plant Science, 2022)
Transient expression of genes encoding peptides BP134 and BP178 by means of a Potato virus X (PVX) based-vector system, and treatment with synthetic peptides by endotherapy, were evaluated in the control of Xylella fastidiosa infections, in the model plant Nicotiana benthamiana. Transient production of BP178 significantly decreased disease severity compared to PVX and non-treated control (NTC) plants, without adverse effects. Plants treated with synthetic BP134 and BP178 showed consistently lower levels of disease than NTC plants. However, the coinfection with PVX-BP134 and X. fastidiosa caused detrimental effects resulting in plant death. The levels of X. fastidiosa in three zones sampled, upwards and downwards of the inoculation/treatment point, significantly decreased compared to the NTC plants, after the treatment with BP178, but not when BP178 was produced transiently. The effect of treatment and transient production of BP178 in the induction of defense-related genes was also studied. Synthetic BP178 applied by endotherapy induced the expression of ERF1, PR1a, PAL, PALII and WRKY25, while the transient expression of BP178 overexpressed the Cath, Cyc, PR4a, 9-LOX and Endochitinase B genes. Both treatments upregulated the expression of PR1, PR3, PR4 and CycT9299 genes compared to the NTC or PVX plants. It was concluded that the effect of BP178, either by endotherapy or by transient expression, on the control of the X. fastidiosa infections in N. benthamiana, was due in part to the induction of the plant defense system in addition to its bactericidal activity reported in previous studies. However, the protection observed when BP178 was transiently produced seems mainly mediated by the induction of plant defense, because the levels of X. fastidiosa were not significantly affected.